The Effect Of Availability And Quality Of Raw Materials On Haspel Production Volume (Case Study At Himas Mekar): - Handi, Isep; Umbara, Dona Setia; Jakiyah, Ulpah (Jurnal Multidisiplin, 2026)
The availability of stable and quality wood raw materials is very important to maintain the smooth production process of haspel, because unstable supply and poor wood quality can hamper production and reduce the quality of the final product. This study aims to analyze the effect of the availability and quality of raw materials on production volume in the haspel plate industry of Himas Mekar Sukaraja. The method used is quantitative research with a case study approach, involving 32 respondents who are directly involved in the production process. The results show that the availability of raw materials (X1) has a significant and positive effect on production volume (Y), where the higher the availability of raw materials, the greater the production volume produced. The quality of raw materials (X2) also has a significant and positive effect on production volume, which means that increasing the quality of wood will increase production output. Simultaneously, both variables of availability and quality of raw materials have a significant effect on production volume, so that increasing both is an important factor in maintaining and increasing the productivity of the haspel industry of Himas Mekar Sukaraja.